A rare case of Hermansky-Pudlak syndrome - Kini, Pushpa G.; Bhatia, Aashna; Balasubramanian, Rukmoni (International Journal of Contemporary Pediatrics, 2023)
Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterised by oculocutaneous albinism, a bleeding diathesis and platelet storage deficiency. Aim of this paper is to report a case of patient with HPS who was followed over a decade. A 2-and-a-half-year-old boy presented with recurrent respiratory tract infections and global developmental delay. On examination, he had light golden hair, grey iris with nystagmus, fundus hypo-pigmented fovea and white macules all over body. Also found to have neutropenia without granules on peripheral smear. HPS can often be diagnostic dilemma mimicking disorders like Chediak-Higashi syndrome (CHS), in this case diagnosis was made due to characteristic skin and hair hypopigmentation and ocular findings along with bleeding diathesis. Our patient categorised under HPS2 subtype which has mild immunodeficiency. HPS is usually associated with neutropenia and hence pyogenic infections, present case however was associated with advanced form of pulmonary tuberculosis-miliary TB and granulomatous TB lymphadenitis giving rise to the possibility of T-cell defect.